Anticoagulant Dependent Pseudothrombocytopenia: A Case Report - Aryal, B; Adhikari, S; Aryal, N; Pant, v (Journal of Institute of Medicine Nepal, 2017)
Pseudothrombocytopenia is a laboratory finding caused by in vitro autoaggregation of platelets (an irreversible change) resulting due to the presence of EDTA in containers. In contrast to serious and potential life-threatening causes of thrombocytopenia, EDTA-pseudothrombocytopenia (EDTA- PTCP) is solely an in vitro effect without any clinical relevance.We report a 24 year old patient from MCTVC hospital who presented with common flu. On blood examination there was low platelets count in EDTA anticoagulated sample but he was clinically otherwise normal and there were no symptoms of thrombocytopenia. On smear preparation, in EDTA and Trisodium citrate sample his all blood countparameters were within normal range. This case highlights the importance of slide preparation.